Superplumes: Beyond Plate Tectonics - Yuen, David A.; Maruyama, Shigenori; Karato, Shun-Ichiro.; Windley, Brian F.; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2007)
This book provides a concise overview of our understanding of the entire mantle, its evolution since early differentiation and the consequences of superplumes for earth surface processes. The balanced, international authorship of the 18 contributions has produced a state-of-the-science report on the emerging concept of superplumes and has documented the potential of superplumes to serve as a testable model for future studies. The topic of superplume dynamics has been treated from different angles covering the sub-disciplines of geology, geochemistry, petrology as well as geophysics (including mineral physics, seismic tomography and mantle dynamics). For instance, it is shown how transport of heat via superplumes, huge stable pipes connecting the high-temperature core with the surface land mass, could have caused mass extinctions and drastic environmental change. Audience: Scientists, researchers and graduate students in geology, geochemistry and geophysics, planetary scientists, astrobiologists and environmental engineers.
The Thermal and Compositional Structure of the Earth -- Multiscale Seismic Tomography of Mantle Plumes and Subducting Slabs -- Seismological Constraints on the Structure of the Earth's Core -- Post-Perovskite Phase Transition and the Nature of the D? Layer -- Post-Perovskite MgSiO3 Investigated by First Principles -- Seismological Evidence and Boundary Layers in the Mantle -- Subduction Zone: The Water Channel to the Mantle -- Fine-Scale Ultra-Low Velocity Zone Layering at the Core-Mantle Boundary and Superplumes -- Global Material Circulation and Petrogenesis of Superplume Rocks -- A Geochemical and Petrological View of Mantle Plume -- Material Circulation through Time: Chemical Differentiation Within the Mantle and Secular Variation of Temperature and Composition of the Mantle -- Dynamics of Superplumes -- Dynamics of Superplumes in the Lower Mantle -- Thermal Conductivity of the Earth's Deepest Mantle -- Thermo-Chemical Structure of the Lower Mantle: Seismological Evidence and Consequences for Geodynamics -- Microscopic Models for the Effects of Hydrogen on Physical and Chemical Properties of Earth Materials -- Plume Dynamics through Earth History -- History of the Pacific Superplume: Implications for Pacific Paleogeography Since the Late Proterozoic -- Plume Winter Scenario for Biosphere Catastrophe: The Permo-Triassic Boundary Case -- Dynamics of Plumes and Superplumes through Time -- Plumes and Superplumes on Mars and Venus -- Tharsis Superplume and the Geological Evolution of Early Mars -- Traits and Evolution of the Tharsis Superplume, Mars -- Plumes and Plume Clusters on Earth and Venus: Evidence from Large Igneous Provinces (LIPs).
Keywords: GEOCHEMISTRY; GEOLOGY; PHYSICAL GEOGRAPHY; MINERALOGY; PLANETOLOGY; GEOSCIENCES; GEOPHYSICS/GEODESY.; MINERALOGY; GEOCHEMISTRY; PLANETOLOGY; HISTORICAL GEOLOGY